Inquiries on sexual orientation, gender identity and expression exploring teacher knowledge and implications on student well-being - Fernandez, Helen Grace Concepcion Q (2018.)
This paper explores teacher knowledge on sexual orientation, gender identity and expression (SOGIE) and its implications on student well-being. This study is not capable of determining correlations between teacher knowledge and student well-being; however, knowledge about SOGIE becomes significant when managing inquiries or concerns of students. this study utilized key informant interviews of teachers and a focus group discussion of students. The Positive Education Practices (PEPs) Framework was utilized as practical assessment of how teachers deal with inquiries pertaining to SOGIE, and how it can influence the classroom environment. It is evident that teachers recognize that their students are seeking for support in finding themselves, guidance on how to deal with interpersonal relationships, and explanations about the vast information fed by the multimedia. Results of this study have shown that SOGIE as a whole is a vague concepts to the teachers, as well as guidance counselors, and their approaches ...
Special Problem (Graduated, Master of Education (Guidance) Division of Professional Education, College of Arts and Sciences
Keywords: Sexual orientation -- Research; Gender identity -- Research